Diffusion of residential RT solar – is lack of funds the real issue?. Issue 2 (18th October 2019) - Aggarwal, Ashwini Kumar; Syed, Asif Ali; Garg, Sandeep
Abstract : Purpose: Rooftop (RT) solar in India has grown to 4.4 GW by the end of March 2019 – but it is still under-performing vs national solar mission target of 40 GW. This paper aims to understand the drivers of the purchase intent (PI) for RT solar will enable policymakers to improve the penetration of this new and promising green technology. Design/methodology/approach: This paper builds a structural equation modeling model for triggers of the PI of a residential RT solar photo-voltaic (SPV) buyer. The empirical study conducted in Delhi/national capital region of Delhi and Bangalore validates the role of the Unified Theory of Acceptance & Use of Technology (2) constructs in the PI of the residential sector RT solar buyer in India. It also explores a few myths – prior green habits have no relationship with the PI and self-efficacy has been dropped in the final path analysis to improve model fit. Findings: This research explores the myth that financial self-efficacy – or prospect's perception of his capability to fund (through own or credit finance) – will mean that the prospect is likely to be more conducive to an SPV purchase in the city contexts studied. It is more relevant for policymakers to work on factors such as social influence/ beliefs, effort expectancy and price-value beliefs. Other relevant triggers are performance expectancy, hedonic motivation and environmental beliefs. Originality/value: This is the first Indian research leveraging multi-city survey of actual households build an empirically verified consumer behavior model for RT SPV in the residential sector leveraging the unified theory of acceptance and use of technology 2 constructs.